2014
DOI: 10.1536/ihj.13-081
|View full text |Cite
|
Sign up to set email alerts
|

Nonculprit Lesion Progression in Patients With ST Elevation Myocardial Infarction After Primary Percutaneous Coronary Intervention

Abstract: SummaryThe majority of cardiovascular events in patients with ST elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary interventions (PPCI) arise from the progression of nonculprit lesions (NCL) during the long-term follow-up period. However, the clinical and angiographic factors related to the progression of nonculprit lesions are unknown.The purpose of the study was to investigate the clinical and angiographic factors related to the progression of nonculprit lesions of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…A clinical follow-up study of such patients after successful PPCI suggested that non-culprit lesions may progress, which may be the most important factor influencing the prognosis of patients with acute myocardial infarction after successful PPCI. 4 Few studies have examined the progression of non-culprit lesions. Hanratty et al 9 demonstrated exaggeration of nonculprit lesions during acute myocardial infarction and indicated that inflammatory and spastic mechanisms may be involved in non-culprit lesion progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A clinical follow-up study of such patients after successful PPCI suggested that non-culprit lesions may progress, which may be the most important factor influencing the prognosis of patients with acute myocardial infarction after successful PPCI. 4 Few studies have examined the progression of non-culprit lesions. Hanratty et al 9 demonstrated exaggeration of nonculprit lesions during acute myocardial infarction and indicated that inflammatory and spastic mechanisms may be involved in non-culprit lesion progression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent clinical studies have shown that PPCI can lead to the progression of non-culprit lesions, which might be the most significant factor influencing the prognosis after PPCI. 4 5 The molecular mechanisms of myocardial ischemia-reperfusion (IR) involve myocyte apoptosis, increased catecholamine levels, and activation of the angiotensin II/mitogen-activated protein kinase/connexin 43 (AgII/MAPK/Cx43) pathway. 6 The reason for the progression of non-culprit lesions in patients with STEMI after PPCI is not clear, but chronic inflammation and sustained stress may be involved in the progression of non-culprit lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Previous studies 23,24) showed beneficial effects of cardiac denervation on infarct size during ischemia. Other studies, however, demonstrated that cardiac denervation had no protective effect on ischemic injury, 25) or rather had a detrimental influence.…”
Section: Effect Of Interstitial Ne Concentration On Ischemiareperfusimentioning
confidence: 99%
“…1,2) It is generally accepted that excess levels of norepinephrine (NE) could lead to myocardial injury. [3][4][5] Prolonged myocardial ischemia releases a large amount of NE from the cardiac sympathetic nerve terminals independent of central sympathetic activation. 6) Therefore, increased levels of interstitial NE (iNE) during myocardial ischemia may be involved in the pathogenesis of I/R injury, and an intervention to reduce iNE may play a role in reducing I/R injury.…”
mentioning
confidence: 99%